Proses Morfologis Kosakata Warna dalam Al-Qur'an - Lidya Nurlaily; Gina Najjah Hajidah (Program Studi Pendidikan Bahasa Arab Unisda Lamongan, 2023)
This research explains the morphological process of colors vocabulary in the Holy Qur'an. The colors mentioned in the Qur'an are mostly basic colors, namely: white, green, black, yellow, red, and blue. Color vocabulary in the Qur'an is expressed in various forms, which is due to the morphological process in the Arabic language. The morphological process that occurs in these color words influences the meaning of the resulting words. The theory used in this research is the theory of morphological process proposed by Prof. Dr. Tajudin Nur (2018). This study uses a literature study method through books, dictionaries, journal articles, and scientific articles. The results of the study explain that the colors vocabulary in the verses of the Qur'an undergo morphological processes through derivation and inflection. Derivation occurs in the colors white, green, black, and yellow, as verb of pattern IX Ø§ÙØ¹Ù„Ù‘ - ÙŠÙØ¹Ù„Ù‘ /ifâ€˜alla-yafâ€˜allu/ from the root of each colors. Other derivations occur from the root of each colors to qualifying adjective pattern with internal changes and to an agentive noun by adding the prefix Ù…Ù /â€“mu/. As for inflection, it occurs in verbs (conjugation) and nouns (declension) through affixation in verbs and internal changes in nouns to indicate gender changes into feminine. Declension also occurs for amount changes to jamak with internal changes. All colors vocabulary in the Holy Qur'an are found in the form of qualifying adjectives, which is the most common form for colors.